Efektivitas Penggunaan Media Pembelajaran Kahoot dalam Meningkatkan Motivasi Belajar Ekonomi Siswa Kelas X di SMA Negeri 13 Medan - Daniaty Nababan, Fera; Siar Meiriza, Mica (SJEE (Scientific Journals of Economic Education), 2025)
The problem in this study is the low motivation of students to learn in the learning process using kahoot media, the lack of implementation of economic learning using kahoot media and whether there is an influence of the use of kahoot media on students' learning motivation. This study aims to determine the motivation of students to learn in the learning process using kahoot media, to determine the implementation of economic learning using kahoot media and to determine the influence of the use of kahoot media on students' learning motivation. There is a difference in the average value between the class before using the media 6% and the class after using the media 76%, it can be seen that the average value in the class after using the media is higher than the average value in the class before using the media (76%> 16%). Then from the results of the r test obtained from r count > r table shows that the value of r table with N = 35 at a significance of 5% in the distribution of r table statistical values .j then the r table value is obtained of 0,334. So there is a significant influence between variable X and variable Y.